Photochemical processes in solutions of uranyl perchlorate in acetone with participation of atmospheric oxygen - Komyak, Anatolij I.; Vilejshikova, Nataliya P; Komyak, Elena N.; Zajogin, Anatolij P. (Journal of the Belarusian State University. Physics, 2017)
The photochemical formation processes of the nanoclusters of tetra- and pentavalent uranium with organic ligands have been studied by the methods of electron and IR absorption under light-emitting diode irradiation (430 – 450 nm) of UO2(ClO4 ) ⋅ 5H2O solutions having different proportions of Ca(NO3 )2 and uranium in the presence and in the absence of oxygen. It has been found that in the systems UO2(ClO4 )2 ⋅ 5H2O in acetone, with the addition of calcium nitrate in acetone, their irradiation in sealed cells leads to photopolymerization of acetone, the excited uranyl complexes being catalysts of the process. During such reactions the photoexcited ions of uranyl are oxidizing one part of the organic molecule and then are oxidized by its other part up to U(VI). In this way the uranyl ions are catalysts of the light activated dismutation reaction. The reactions of both types may take place in the absence of oxygen as well. Spectra of the same samples irradiated in the cells with the access of atmospheric oxygen reveal the bands attributed to the tetra- and pentavalent uranium complexes, i. e. in the presence of oxygen there is a possibility for the reaction of the third type – sensibilized autooxidition of the organic reducing agent and the accompanying reduction of U(VI) up to U(V) and U(IV).
Keywords: uranyl perchlorate; acetone; electron absorption spectra; IR absorption spectra; photochemical processes; tetravalent uranium complexes; pentavalent uranium complexes; nanoclusters